2017
DOI: 10.1055/s-0037-1606826
|View full text |Cite
|
Sign up to set email alerts
|

Early-Career Surgical Practice for Cerebellopontine Angle Tumors in the Era of Radiosurgery

Abstract: We analyzed the outcomes of patients with large cerebellopontine angle (CPA) tumors treated by a skull-base team in which two surgeons (one neurosurgeon and one otological surgeon) were in the beginning of their careers (<40 years old). Data of patients operated on between April 2012 and March 2016 were reviewed. All factors related to surgical training were considered. Thirty-one patients had vestibular schwannomas, while 26 had meningiomas. Mean tumor diameter was 30.6 mm (range, 23-49 mm) for schwannomas an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 34 publications
0
6
0
Order By: Relevance
“…They are characterized by the deep tumor location, narrow surgical field, and proximity to the brainstem, multiple pairs of (V–XI) cranial nerves ( 2 ). At present, surgical treatment is the first choice for large cerebellopontine angle meningiomas, while small cerebellopontine angle meningiomas are always treated by stereotactic radiotherapy, pharmacotherapy and experimental therapy ( 3 ). In recent years, many studies have found that stereotactic radiotherapy had the limitations of low tumor control rate, post-treatment brain edema, and tissue adhesion, which hindered the further treatments ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…They are characterized by the deep tumor location, narrow surgical field, and proximity to the brainstem, multiple pairs of (V–XI) cranial nerves ( 2 ). At present, surgical treatment is the first choice for large cerebellopontine angle meningiomas, while small cerebellopontine angle meningiomas are always treated by stereotactic radiotherapy, pharmacotherapy and experimental therapy ( 3 ). In recent years, many studies have found that stereotactic radiotherapy had the limitations of low tumor control rate, post-treatment brain edema, and tissue adhesion, which hindered the further treatments ( 4 ).…”
Section: Introductionmentioning
confidence: 99%
“…[4][5][6] However, it still has always proven arduous for neurosurgeons to optimally accomplish, 7 because of their complex anatomical regions, the deep and narrow surgical channels related, and lots of critical neurovascular structures in the surgical field. 8 Cerebellar retraction is an inevitable and frequent step when performing microsurgery of CPAMs via the retrosigmoid approach. Many complications have been reported due to this retraction, including postoperative posterior fossa edema, cerebellar contusions, injury of the stretched cranial nerves, and ischemic injuries of the cerebellum and perhaps even the brain stem.…”
Section: Discussionmentioning
confidence: 99%
“…The conventional surgical approaches of CPAMs in neurosurgery include suboccipital retrosigmoid approach, enlarged retrosigmoid approach, presigmoid approach, combined supratentorial approach, and so on 4–6. However, it still has always proven arduous for neurosurgeons to optimally accomplish,7 because of their complex anatomical regions, the deep and narrow surgical channels related, and lots of critical neurovascular structures in the surgical field 8. Cerebellar retraction is an inevitable and frequent step when performing microsurgery of CPAMs via the retrosigmoid approach.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CPA has always proven difficult for neurosurgeons to optimally manage,[ 1 ] also challenging to resect because of their complex regional anatomy, the deep and narrow surgical corridors involved, and the abundance of vital neurovascular structures in the surgical field. [ 25 ] The posterior fossa venous anatomy is often not well visualized during surgery. This is particularly true regarding the SPVC.…”
Section: Discussionmentioning
confidence: 99%